北極域研究・観測拠点:カナダ極北研究ステーション(CHARS)における研究について - 末吉, 哲雄; 宮岡, 宏; 榎本, 浩之; Tetsuo, Sueyoshi; Hiroshi, Miyaoka; Hiroyuki, Enomoto (2017)
第8回極域科学シンポジウム/横断セッション：[IA] 北極国際連携拠点の新展開 12月8日（金）国立極地研究所 2階大会議室 The Eighth Symposium on Polar Science/Interdisciplinary sessions: [IA] New insights of overseas research stations in the Arctic Fri. 8 Dec./2F Auditorium, National Institute of Polar Research conference object